Formation of ionospheric sporadic E layers by atmospheric gravity waves - Didebulidze, Goderdzi G.; Dalakishvili, Giorgi; Lomidze, Levan; Matiashvili, Giorgi (Journals of Georgian Geophysical Society, 2015)
In this work the formation of mid-latitude sporadic E (Es) layer under the influence of atmospheric gravity waves (AGWs) evolving in the horizontal shear flow is studied. AGWs can be excited in the background horizontal wind with a linear horizontal shear (horizontal shear flow). These in-situ excited atmospheric waves, which act on metallic ions through ion-neutral collisions and Lorentz forcing, influence the ion vertical motion and can lead to their convergence into thin horizontal layers. The formation of sporadic E is investigated using a numerical model in two-dimensional case and temporal evolution of multi-layered sporadic E is demonstrated. The ion/electron density of Es layers depends on the amplitude of AGWs and spatial location of the layers is determined by the vertical wavelength of atmospheric gravity waves.